Improving Writing Skill of Narrative Text by Using Short Video at SMA Negeri 1 Silau Kahean - Catri Novita F. Manalu; Mila Kristi Sitopu; Ayu Paulina Silaban; Natalia Widya Pasca Tarigan (Journal of Languages and Language Teaching, 2021)
Video technology in ELT has been increasingly used to help students to improve their language skills. Various videos are designed to present ELT materials. This study aims to investigate the use of short videos to improve students’ writing skills of narrative texts at the senior high school. This study is categorized as classroom action research. The data consist of qualitative and quantitative data. The instruments used to attain the qualitative data are observation and documentation, while the quantitative data are collected using writing tests. This study is carried out in two cycles. The use of short videos helps students understand the generic structures of narrative texts. During learning processes, students are asked to analyze the narrative structures from the introductory to the conclusion paragraph. The improvement of students’ narrative texts is made in the second cycle. The students’ writing achievement is 76.25 in the second cycle. The students’ achievement achieves the passing grade. Therefore, the use of short videos is able to improve students’ writing skills of narrative texts at the senior high school.